2021
DOI: 10.3390/cells10113138
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Topoisomerase II Inhibitor with Dose-Affected Anticancer Mechanisms and Less Cardiotoxicity

Abstract: Type II DNA topoisomerase (topo II) is an essential nuclear enzyme and a well-validated anticancer drug target. Previously, we have carried out several rounds of structural optimizations on our in-house topo II inhibitor E17, which was shown to have superior anticancer activity and less risk of multidrug resistance (MDR). Among the newly developed acridone derivatives, 6h displayed significant anticancer efficacy with unique mechanisms of action. At low concentrations, it arrested cancer cell cycles and trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The limitation to this work was that no standard drug was used to compared against the activity of the synthesized compounds on the 9 cancer panels, and actual assay for TopoIIα was not conducted. Moreover in China, Li et al [55], reported that newly developed acridone derivatives, 1-((3-(dimethylamino)propyl)amino)-7-hydroxy-4-nitroacridin-9(10H)-one, could inhibit TopoIIα, intercalates with DNA, and showed significant and long-term anti-proliferative activity at relatively high concentrations. Previous studies have identified several acridone derivatives as TopoII inhibitors and DNA intercalator with cell cycle arrest and apoptosis [56,57].…”
Section: -(4-(acridin-9ylamino)-phenyl)-1h-123-triazol-1-yl)-n-hydrox...mentioning
confidence: 99%
“…The limitation to this work was that no standard drug was used to compared against the activity of the synthesized compounds on the 9 cancer panels, and actual assay for TopoIIα was not conducted. Moreover in China, Li et al [55], reported that newly developed acridone derivatives, 1-((3-(dimethylamino)propyl)amino)-7-hydroxy-4-nitroacridin-9(10H)-one, could inhibit TopoIIα, intercalates with DNA, and showed significant and long-term anti-proliferative activity at relatively high concentrations. Previous studies have identified several acridone derivatives as TopoII inhibitors and DNA intercalator with cell cycle arrest and apoptosis [56,57].…”
Section: -(4-(acridin-9ylamino)-phenyl)-1h-123-triazol-1-yl)-n-hydrox...mentioning
confidence: 99%